2011
DOI: 10.1016/j.freeradbiomed.2011.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 regulates Nrf2 and glutathione redox in cardiomyocytes in vivo

Abstract: NADPH oxidase-4 (Nox4) is an important modulator of redox signaling that is inducible at the level of transcriptional expression in multiple cell types. By contrast to other Nox enzymes, Nox4 is continuously active without requiring stimulation. We reported recently that expression of Nox4 is induced in the adult heart as an adaptive stress response to pathophysiological insult. To elucidate the potential downstream target(s) regulated by Nox4, we performed a microarray screen to assess the transcriptomes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 67 publications
4
107
0
Order By: Relevance
“…-/ -background (17). This demonstrates that, while an initial stimulus might be oxidative in nature, the response of the cell can subsequently result in an overall more reducing cellular environment.…”
Section: Brewer Et Almentioning
confidence: 91%
See 2 more Smart Citations
“…-/ -background (17). This demonstrates that, while an initial stimulus might be oxidative in nature, the response of the cell can subsequently result in an overall more reducing cellular environment.…”
Section: Brewer Et Almentioning
confidence: 91%
“…Nrf2 is subject to activation by ROS, which act to regulate its localization, phosphorylation, and protein degradation (13). Levels of Nrf2 expression correlate with genes encoding the pentose phosphate pathway responsible for NADPH production, supporting its transcriptional control by redox-dependent mechanisms (17). We have preliminarily determined that oxidative stress precedes the development of reductive stress, but direct evidence either for this exclusive relationship or for the reciprocal relationship remains speculative.…”
Section: Ros Reductive Stress and Nrf2 Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…8,19 However, NOX4 may participate to oxygen sensing and exhibit anti-inflammatory properties via regulation of the NRF2 pathway in the heart. 15,20 To determine the role of NOX4 and NOX2 in kidney fibrosis progression, we performed unilateral ureteral obstruction (UUO) on wild-type (WT), and NOX4 knockout (KO) mice as well as on NOX2 and NOX4/NOX2 KO mice. Indeed, UUO is a well described model of renal tubular stress leading to kidney fibrosis.…”
mentioning
confidence: 99%
“…In a model overload it was found that the increased expression of Nrf2 decreased myocardial hypertrophy, cardiac fibroblasts and ROS production, the latter, most likely by modulating the activity of Nox4 [54]. Although the sharp increase in the Nrf2 content is cardioprotective, to modulate the production of ROS, apparently chronic activation may have a contrary effect called "reductive stress", so more studies on their impact is required.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%